DINAMIKA HUKUM DAN KEBEBASAN BERPENDAPAT DI MEDIA SOSIAL: STUDI KOMPARASI ANTARA INDONESIA DAN MALAYSIA - Sugiarto, Ihwan; Badruzaman, Dudi (Masalah-Masalah Hukum, 2024)
The problem or gap in this research is highlighting the legal regulations of the two countries and looking at the similarities and differences in freedom of opinion on social media. The aim of this research is to examine how legal protection of human rights affects the ability to express oneself freely on social media. The methodology used in this research is normative law or library research techniques (library search) and a qualitative approach. The results of this research show that the rules regulated in the Malaysian constitution have given rise to laws that tend to be more assertive and defensive towards the government. Meanwhile, in Indonesia, there have been many reforms in legal regulations following the 1998 Reformation events. However, the similarity between these two countries is that they both provide guarantees to their citizens to freely express their opinions, both orally and in writing